'La Città ideale' as a Set of New Institutionalized Resources Integration Practices—Insights from a Pilot Project of the Sicily Region. (November 2021) - Fulco, Irene; Carrubbo, Luca; Megaro, Antonietta; Liani, Francesca
This study aims to investigate whether and how institutions can contribute to generate value at a territorial level and in which way this value may fit with value-in-business. Starting from the conceptualization of value generation and its relationship with territorial development according to service ecosystem perspective, this study aims to present and discuss an experimental project carried out in a specific Italian area to better understand these main theoretical issues. Specifically, the Sicily region is significant for the genetic factors of the context, linked to a social and cultural structure which, despite the presence of numerous obstacles to socio-economic development, strengthen the path of 'multi-actor and multi-level' involvement, which implies the active participation of a plurality of local actors essential to generate value for the territory and for business.